If g(x)= -4x^2-3x+2, determine g(-2)?

Algebra 1, August 2019 Regent exam

Answer and Explanation:

We have a function g of x, where x can be any number or variable. To calculate g(-2), all we need to do is to plug in -2 in the equation everywhere we see x.

Therefore, this equation becomes g(-2)= -4(-2)^2-3(-2)+2 = -4(4)+6+2= -8

The answer for this problem is -8

Hint: Every time we have a function such as g(x) and are asked to calculate g of something, we just plug that something instead of x.

Let's take a look at a couple of other examples.

Lets say we have f(x) = 3x-5

Let's now calculate f(3), f(2a) and f(3b-4)

Again, we need to keep in mind wherever we see x, just plug in the new value we see in parenthesis for the function.

f(3) = 3(3)-5 = 4

f(2a) = 3(2a)-5 = 6a-5

f(3b-4) = 3(3b-4) -5 = 9b-12-5= 9b-17

At Transformation Tutoring we have incredible ** Math Tutors** who are passionate about education and helping students achieve their dreams. We work in Brooklyn, Queens, Manhattan and online.

For inquiries please call 646-407-9078. Our math tutors specialize in: Geometry, Calculus I, II and III, Linear Algebra, Algebra, Trigonometry, Probability and many more.